EFFICIENCY ASSESSMENT OF THE ADDITIONAL DRINKING WATER TREATMENT WITH HOUSEHOLD CARTRIDGES - Bolshak, A. P.; Mitchenko, T. Ye.; Mitchenko, A. O. (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2020)
The purpose of this study was to rate the performance of cartridges for commercially available pitcher filters. The design features and composition of cartridge loadings of industrial pitcher filters were studied and a comparative study of their performance in terms of water purification from chlorine, hardness ions and organic compounds was made. It is established that all the studied industrial cartridges are physicochemical analogues and differ only in design parameters, and the main factor that influences the degree of water purification from pollutants is the contact time of water with the cartridge loading. It was also found that the information provided by the industrial cartridge manufacturers about the effectiveness of water purification from impurities is untrue and in fact is overstated. The analysis of information on the work of industrial cartridges showed the possibility of a significant increase in their efficiency by creating optimal operating conditions. Requirements have been formulated, that have to be met by the filter cartridge with the optimal properties and the main variable and constant factors that affect the performance of the cartridges are identified.